PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN MAKANAN CEPAT SAJI - Lashwaty, Nina Dewi; Widiati, Ina Sholihah (Sekolah Tinggi Ilmu Ekonomi Semarang, 2025)
The research was conducted at the Hisana Fried Chicken-Cemani. The aim was to reveal the simultaneous and independent impact of consumer behavioral factors : cultural, social, personal, and psychological factors on purchasing decisions for Hisana Fried Chicken-Cemani products. It was also to reveal the factors that have the most impact on product purchases at the outlet. A combination research method was applied. Primary data were obtained through questionnaires, observations, interviews. From the Multiple Linear Regression Analysis personal and psychological factors have a positive regression coefficient sign, while cultural and social factors have a negative sign. Based on ANOVA, there was no simultaneous impact of consumer behavioral factors on purchasing decisions. From the t-test did not reveal an independent impact of cultural, social, personal, or psychological factors on purchasing decisions. Observations revealed that consumers come from Cemani area surrounding the outlet, making place the most impactful factor in purchasing decisions. In-depth interviews also revealed that place was the most impactful factor in purchasing decisions. The findings of this research are not consumer behavioral factors that impact purchasing decisions, but rather the place, which is one of the marketing mix elements that has the most impact on purchasing Hisana Fried Chicken-Cemani products.